PERTUMBUHAN VEGETATIF BIBIT TEBU (Saccharum Officinarum L.) DENGAN PEMBERIAN LCPKS PADA TANAH GAMBUT - Rosmalinda; sopiana; Nurhayati (Journal of Agro Plantation (JAP), 2022)
Peatland is one type of wetland ecosystem that has a low fertility level. Efforts that can be made to increase the nutrient content of peat soils are adding organic fertilizers. Palm Oil Mill Liquid Waste (LCPKS) is one of the organic fertilizers that has a high organic matter content. LCPKS contains a number of nutrients : N, P, K, Ca and Mg. The research method used was experimental with a completely randomized design. The treatment consisted of giving LCPKS with a dose of: 0 mL/polybag (L1); 100 mL/polybag (L2); and 200 mL/polybag (L3) repeated 5 times. Parameters observed consisted of soil pH before and after adding LCPKS, stem diameter, number of leaves, plant height and root dry weight. Based on the results of analysis of variance, LCPKS administration had a significant effect on plant height, stem diameter, number of leaves and pH value. The results of the BNT test showed that giving LCPKS 200 mL/polybag gave the best results on all observation parameters.